2019
DOI: 10.7554/elife.43983
|View full text |Cite
|
Sign up to set email alerts
|

Cellular entry and uncoating of naked and quasi-enveloped human hepatoviruses

Abstract: Many ‘non-enveloped’ viruses, including hepatitis A virus (HAV), are released non-lytically from infected cells as infectious, quasi-enveloped virions cloaked in host membranes. Quasi-enveloped HAV (eHAV) mediates stealthy cell-to-cell spread within the liver, whereas stable naked virions shed in feces are optimized for environmental transmission. eHAV lacks virus-encoded surface proteins, and how it enters cells is unknown. We show both virion types enter by clathrin- and dynamin-dependent endocytosis, facili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
86
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 78 publications
(87 citation statements)
references
References 56 publications
(112 reference statements)
0
86
0
1
Order By: Relevance
“…HAV entry and uncoating remain poorly explained given the exceptional stability of the hepatovirus capsid (8,9). We believe that it is important not to conflate the concepts of attachment factors and receptors for this picornavirus.…”
mentioning
confidence: 98%
“…HAV entry and uncoating remain poorly explained given the exceptional stability of the hepatovirus capsid (8,9). We believe that it is important not to conflate the concepts of attachment factors and receptors for this picornavirus.…”
mentioning
confidence: 98%
“…This has been demonstrated for the HAV, Poliovirus, Coxsackievirus, Rhinovirus, or murine Norovirus [ 3 , 10 , 46 ], which suggests that EV membranes get disrupted following endocytosis, possibly by endosomal lipases and lipid extractor proteins. Consistent with this hypothesis, depletion and pharmacological inhibition of the cholesterol transporter Niemann–Pick disease type C1 (NPC1) protein and the lysosomal acid lipase (LAL), significantly impaired EV-associated HAV and HEV but not naked HAV and HEV infection [ 47 , 48 ].…”
Section: Entry Of Ev-associated Virionsmentioning
confidence: 98%
“…It has been reported that HCV receptor candidates, such as HAV cellular receptor 1 (HAVcr-1), integrin β1, and gangliosides, are the entry receptor candidates for HAV. Further studies in this vein are needed [ 106 , 107 , 108 ]. Gangliosides seem to function as endosome receptors for infection using both naked and quasi-enveloped HAV virions [ 108 ].…”
Section: Prevention Of Hav Infection In Patients With Chronic LIVmentioning
confidence: 99%